Sustainibility in Financial: Cash Management Student in Preventing Financial Distress - Syam, Hasnidar; Ma’ruf, Tri Abriana; Yusuf, Arni Neneng Suriyani; Sasfira, Besse Ade (Celebes Journal of Community Services, 2024)
This research aims to improve students' financial literacy and financial independence through International Community Service activities focused on cash management education and digital-based financial management. This activity was carried out by involving students who are members of the Indonesian Student Association (PPI) at Universiti Kebangsaan Malaysia (UKM), Selangor, through interactive training that includes material delivery, introduction to financial recording applications, budgeting practices, and financial consultations. The methods used included live presentations, online seminars, and discussion sessions. The results showed increased students' understanding of the basics of cash management, the importance of consistent financial recording, and the use of digital applications to support financial management. Students became more disciplined in budgeting, managing expenses, and forming sustainable financial habits. In addition, this program succeeded in building awareness of the importance of financial planning to prevent the risk of financial distress that can affect mental, emotional, and academic well-being. It also provided long-term benefits by creating an active financial discussion community through online groups and educational modules that can be accessed continuously. The findings confirm the importance of digital-based educational approaches in supporting students' financial literacy and the potential for replicating similar programs to create a broader impact. The study recommends further cash flow management and budgeting training, supported by ongoing online consultation services.